Estudo sobre os efeitos anti-inflamatórios do ácido trans-cinâmico - Santos, Samário Lino dos (2018)
Inflammation is a physiological response of vascularized tissues initiated by chemical, physical or biological aggression, which aims to eliminate the initial cause and repair tissue damage. However, the inflammatory response can be triggered inappropriately or be out of physiological limits, contributing to the development of several types of disease. Development of anti-inflammatory drugs remains an important process for therapeutics due to some available drugs side effects. In this regard, natural products are a significant source of bioactive molecules that are usually utilized in the treatment of a large number of diseases. Among compounds found in natural sources, phenolic acids have a large variety of relevant pharmacological effects. The cinnamic acid, a polyphenol compound found in soy, coffee, apple, olive and others, have been reported as a suppressor of lipid peroxidation and tumor cell growth. However, cinnamic acid effects on the inflammatory response still poorly described. Therefore, the present study aimed to evaluate cinnamic acid effects on inflammatory response in vivo and in vitro. To achieve this purpose, models of carrageenan and prostaglandin E2 induced mouse paw edema, lipopolysaccharide (LPS) induced pleurisy and in vitro assays us-ing human neutrophils were used. Results showed that cinnamic acid (in concentra-tions of 5, 50 and 100 mg/kg) significantly reduced carrageenan induced edema for-mation. In the LPS induced pleurisy, treatment with cinnamic acid at 10 mg/kg concen-tration significantly decreased neutrophil influx to the inflammatory site. In vitro neutro-phil treatment with cinnamic acid inhibited TNF-α induced neutrophil adhesion and shape change without interfering with reactive oxygen species generation nor cell via-bility. Thus, these results showed trans-cinnamic acid potential in decreasing inflam-matory response by reducing edema formation and neutrophil motility in vivo and its activation profile in vitro.